The World Bank Group and the Global Food Crisis : An Evaluation of the World Bank Group Response - Independent Evaluation Group (Washington, DC: World Bank Group, 2014)
The unanticipated spike in international food prices in 2007-08 hit many developing countries hard. The World Bank (International Bank for Reconstruction and Development and International Development Association) organized rapidly for short-term support in the crisis, launching a fast-track program of loans and grants, the Global Food Crisis Response Program (GFRP). The GFRP mainly targeted low-income countries, and provided detailed policy advice to governments and its own staff on how to respond to the crisis. The Bank also scaled up lending for agriculture and social protection to support the building of medium-term resilience to future food price shocks. The International Finance Corporation (IFC) responded by sharply increasing access to liquidity for agribusinesses and agricultural traders in the short and medium term, as well as new programs to improve incentives for agricultural market participants. This evaluation assesses the effectiveness of the World Bank Group (WBG) response in addressing the short-term impacts of the food price crisis and in enhancing the resilience of countries to future shocks. Bank group support for the short-term response reached vulnerable countries, though it is less clear whether it reached the most vulnerable people within countries. The program supported 35 countries, with Sub-Saharan Africa accounting for about 60 percent of funding. The majority of support went to four countries-Bangladesh, Ethiopia, the Philippines, and Tanzania. The speed of the response often had costs for quality, and design deficiencies could not always be rectified quickly during implementation. The Bank's short-term assistance to agriculture took the form of input subsidy and distribution operations to increase food supply. Short-term support for social safety nets mainly consisted of in-kind transfers and public works programs. The Bank's medium-term response for agriculture significantly increased lending and focused on expanding productive capacity and resilience.